Galatians 3.10-12: Assumptions and Argumentation - Hunn, Debbie (Journal for the study of the New Testament, 2015)
To follow Paul’s argument in Gal. 3.10-12 requires resolving the controversy over whether he makes the implicit assumption in v. 10 that no one is able to keep the law. The contention of this article is that Paul does not build upon this idea as a presupposition, because his argument would then rest on a concept that his audience denies. Instead, he proves this point in vv. 11-12 on the basis of an implicit assumption that he shares with his readers: the law either justiﬁes or condemns; there is no third option. Because the law does not justify anyone, it therefore condemns everyone under it; the people it condemns are exactly the people who break it.